2020
DOI: 10.1016/j.clinph.2020.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of high frequency oscillations as a biomarker of the seizure onset zone

Abstract: Objective: Studies of high frequency oscillations (HFOs) in epilepsy have primarily tested the HFO rate as a biomarker of the seizure onset zone (SOZ), but the rate varies over time and is not robust for all individual subjects. As an alternative, we tested the performance of HFO amplitude as a potential SOZ biomarker using two automated detection algorithms.Method: HFOs were detected in intracranial electroencephalogram (iEEG) from 11 patients using a machine learning algorithm and a standard amplitude-based … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 45 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…In particular, based on the analysis of time-frequency plots of eHFOs and non-eHFOs, eHFOs showed stronger signals throughout ripple and fast ripple bands at the onset of HFOs, which shares the similar observation in HFOs seen at the SOZ. 49 Meanwhile, eHFOs generally showed stronger signals in the low frequency region throughout the time window, which might represent an inhibitory slow-wave postsynaptic component, coupled with out-of-phase excitatory fast firing of HFOs. 50 Taking advantage of these observations, we designed perturbations in the input to probe whether these characteristics were actually the salient features that the model relied on to make a prediction.…”
Section: Discussionmentioning
confidence: 97%
“…In particular, based on the analysis of time-frequency plots of eHFOs and non-eHFOs, eHFOs showed stronger signals throughout ripple and fast ripple bands at the onset of HFOs, which shares the similar observation in HFOs seen at the SOZ. 49 Meanwhile, eHFOs generally showed stronger signals in the low frequency region throughout the time window, which might represent an inhibitory slow-wave postsynaptic component, coupled with out-of-phase excitatory fast firing of HFOs. 50 Taking advantage of these observations, we designed perturbations in the input to probe whether these characteristics were actually the salient features that the model relied on to make a prediction.…”
Section: Discussionmentioning
confidence: 97%
“…One possible approach is to examine HFO morphological features, such as amplitude, duration, and spectral frequency (Chen et al, 2021). When comparing HFO events detected in the epileptogenic vs. nonepileptogenic tissues, ripples showed larger amplitude, longer duration and lower frequency (von Ellenrieder et al, 2016, Charupanit et al, 2020, FR consistently showed larger amplitude but either shorter (Pail et al, 2017) or longer duration (von Ellenrieder et al, 2016) in the MTL, while neocortical HFO detected in the full spectral range showed either larger (Guragain et al, 2018) or lower amplitude (Alkawadri et al, 2014). In this study, rather than focusing on the statistical evaluation of the individual HFO morphological feature, we considered their multivariate information.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, based on the analysis of time-frequency plots of eHFOs and non-eHFOs, eHFOs showed stronger signals throughout ripple and fast ripple bands at the onset of HFOs, which shares the similar observation in HFOs seen at the SOZ. 48 Meanwhile, eHFOs generally showed stronger signals in the low frequency region throughout the time window, which might represent an inhibitory slow-wave postsynaptic component, coupled with out-of-phase excitatory fast firing of HFOs. 49 Taking advantage of these observations, we designed perturbations in the input to probe whether these characteristics were actually the salient features that the model relied on to make a prediction.…”
Section: Discussionmentioning
confidence: 97%